(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Takarina ND, Nurliansyah W, Wardhana W. 2019. Relationship between environmental parameters and the plankton community of the Batuhideung Fishing Grounds, Pandeglang, Banten, Indonesia. Biodiversitas 20: 171-180. Phytoplankton has a role as primary producers and zooplankton as primary consumers in the marine environments. The composition of the plankton community is dependent on the physical and chemical characteristics of the waters. The aim of the research described here was to analyze the community structure of plankton in the Batuhideung Fishing Grounds, of Banten in Indonesia, and to relate this structure to the physical parameters (sea surface temperature, clarity, current velocity) and chemical parameters (salinity, pH, DO, nitrate, phosphate) of its sea surroundings. The research was conducted three times at five observation stations from September to October 2017. Samples of phytoplankton and zooplankton were taken horizontally using nets with mesh size of 80 ?m and 133 ?m, respectively. Results showed that the sea surface temperature ranged from 28.70-30.20?C, current velocity 0.10-1.30 m/s, clarity 7-10 m, salinity 30-34 g/L, DO 6.20- 8.60 mg/L, pH 8.40-8.59, nitrate concentration 0.49-0.81 mg/L, and phosphate concentration 0.09-0.42 mg/L. There were 37 genera from 4 classes of phytoplankton. The abundance of Bacillariophyta was 52,734 individuals/L, Myzozoa was 1,315 ind/L, Chyanophyta was 633 ind/L, and Euglenophyta was 200 ind/L. There were 35 genera from 12 classes of zooplankton, dominated by Copepods with abundance 82.1-91.4%. The diversity index of phytoplankton ranged from 1.25-2.02, evenness index ranged from 0.52-0.85, and dominance index ranged from 0.19-0.38. Based on multivariate cluster analysis, there were similar environmental parameters in stations 1, 2 and 3, while stations 4 and 5 grouped differently from the other three. Based on Pearson’s correlation analysis, current velocity and phosphate were positively correlated to phytoplankton abundance, whereas temperature, transparency, salinity, DO, pH, and nitrate were negatively correlated, temperature significantly so. Nitrate, phosphate, salinity, DO were positively correlated with zooplankton abundance but not significantly. Temperature, current velocity, clarity, and pH were negatively correlated with zooplankton abundance, but only with pH did the correlation reach statistical significance.